Logistic Service Efficiency Using Value Stream Mapping Approach in the Pharmacy of Class-I Prison Clinic, Malang - Salsabilah, Nabilah; Sri Redjeki, Endang; Tristanti Puspitasari, Sendhi (KnE Life Sciences, 2021)
A clinic is a healthcare facility providing basic services for individual health, a pharmacy is one of the installations of a clinic. The task of a pharmacy as a unit of a clinic is to organize, coordinate, manage and supervise all pharmacy-related services. The logistics management activities at the Class-I Prison Clinic of Malang include planning, requesting, receiving, storing, distributing, controlling, recording and reporting, as well as monitoring and evaluation. The current research was conducted on the four activities of requesting, receiving, storing and distributing. This study utilized the Value Stream Mapping (VSM) theory as an effort to reduce waste. The study used a quantitative descriptive method with a cross-sectional design. A total of 97 samples including workers involved in logistics management activities and patients seeking treatment were chosen using an accidental sampling method with the Taro Yamene formula. Data were collected through documents, interviews and observations. The results obtained in the distribution process considered all four activities, however, there was still some waste during the process. The calculated value added ratio (VAR) was 61.46%, which means that the clinic implements a lean management. Keywords: logistic management, distribution, value stream mapping, drugs